2018
DOI: 10.1371/journal.pone.0198908
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset preeclampsia predisposes to preclinical diastolic left ventricular dysfunction in the fifth decade of life: An observational study

Abstract: BackgroundSystemic inflammation, endothelial dysfunction and deficient vascularization of either uterus or myocardium are mechanistic hallmarks of early-onset preeclampsia and heart failure with preserved ejection fraction (HFpEF). HFpEF is especially prevalent in elderly women and preceded in middle age by preclinical left ventricular (LV) diastolic dysfunction.To detect if preeclampsia predisposes to HFpEF at later age, echocardiographic indices of LV function and of LV structure and biomarkers of systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
2
43
0
Order By: Relevance
“…13 An alternative proposed by Wu et al is that pre-eclampsia unmasks early cardiovascular disease, a failure of the pregnancy 'stress test'. One is that pre-eclampsia and cardiovascular disease share an aetiology of systemic inflammation, endothelial dysfunction and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13 An alternative proposed by Wu et al is that pre-eclampsia unmasks early cardiovascular disease, a failure of the pregnancy 'stress test'. One is that pre-eclampsia and cardiovascular disease share an aetiology of systemic inflammation, endothelial dysfunction and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, biventricular systolic dysfunction, severe hypertrophy, left atrial dilatation and global diastolic dysfunction can all be observed in both pre-eclampsia and essential hypertension. 13 Orabona et al specifically excluded from their study women with cardiovascular risk factors (smoking, dyslipidaemia, overweight/obesity, diabetes mellitus, or chronic hypertension) and only included women who had remained normotensive 6 months post-partum. 10 However, the two studies in this review looking at incidence of HF-B post-partum did not find any association between HF-B and hypertension, or other metabolic syndrome constituents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations